Formação de professores no contexto da (re)introdução da Língua portuguesa em Timor-Leste: da polêmica às ações táticas - SANTOS, Fabiana Almeida dos (Universidade Federal do Pará, 2014)
This research investigates how students translate and interpret the discourse of the reintroduction of the Portuguese Language in East Timor. The students are learning this language as part as the training course named Bachelor of Natural Sciences degree, that was offered by a Brazilian cooperation from October 2009 to December 2010. The research is based on data produced or reconstituted from my experience as a teacher in this course that was promoted by the "Program for Teacher Qualification and Portuguese Language Teaching (PQLP) coordinated by CAPES Foundation. For data discussion, I use as theoretical and methodological tools: Maingueneau concepts (2008), especially "interincomprehension" and "simulacrum"; and the concepts of “strategy” and “tactics” by Michel de Certeau (2012), which compose his polemologico model of cultural appropriation. The analysis suggests that the way course participants and trainers appropriate themselves in the reintroduction policy of discourse of the Portuguese Language in East Timor is determined by different discursive formations and that the interdiscursive relationship established between them cause the phenomenon of "interincomprehension". Understanding how these discursive formations translate themselves into the classroom, in teaching and learning the Portuguese Language activities, can contribute to (re)define the educational interventions in the Portuguese classes in the teacher training course and the policy of reintroduction of the Portuguese Language in East Timor. We argue that the teaching and learning of the Portuguese Language in East Timor need to be understood not only from the didactic point of view, with regard to the construction and mediation of knowledge between students and teachers, but also from the ideological point of view, since the current teachers training programs in this country, represent a project that may conflict with the society’s values and beliefs about the Portuguese Language and the relationship between the school and other institutions.